Neurocognitive assessment of alcohol inpatients during recovery from alcoholism - Šprah, Lilijana (Zdravniški vestnik, 2008)
Objective The aim of study was a neuropsychological evaluation of cognitive, emotional and motivational functioning of abstinent alcohol inpatients. Background Alcohol dependence is characterized by a neuropsychological profileof extensive impairment in executive functions, visuospatial abilities,sociocognitive, emotional and motivational dysfunctions. A growing body of research evidence suggests that alcoholism-related structural and functional brain changes may underlay abovementioned deficits. Nevertheless, certain alcohol-related impairments are reversible with abstinence. Several studies indicated that with prolonged abstinence functional improvement in memory, visuospatial abilities, and attention occur within 3 to 4 weeks of abstinence accompanied by at least partial reversal of brain shrinkage and some recovery of metabolic functions in the frontal lobes and cerebellum, as well as with increased cortical grey matter volume. Methods 33 male abstinent alcohol inpatients (average abstinence: 8 weeks) and 36 healthy controls were tested on the following domains: attention (classical vs. emotional Stroop Task), working memory (spatial vs. verbal), visuospatial abilities (Benton Face Recognition Task, Line Orientation Test), emotionality (Ekman Emotional Recognition Task, Test of Emotional Styles, Beck Depression Inventory) and motivation (Behavioural Inhibition/Activation Scale). Results Alcohol abstainers compared to healthy controls showed impaired attention, more depressive symptoms and overactive activation behavioural system, whereas the working memory and visuospatial tasks did not reveal significant differences between groups. A specific neuropsychological profile has been found among alcohol abstainers with suicidal history where lower emotion recognition ability and attention difficulties with emotional stimuli have been recorded. (Abstract truncated at 2000 characters)
Keywords: abstinenca; Alcoholism; Alkoholizem; Cognition Disorders; Diagnosis; neuropsychology; nevropsihologija; odvisnost; Osebnostni testi; Personality Tests; Spoznavne motnje; Temperance; Treznost